Dydaktyczny charakter biblijnej księgi na przykładzie Deuteronomium - Renata Jasnos (Nicolaus Copernicus University in Toruń, 2012)
Deuteronomy as a biblical text expresses tradition which was being developed for a few centuries. Its creators used a model taken from the world of ancient pedagogy to present the dynamic relation between God and Israel. Deuteronomy consists of the traditions coming from the wisdom current, and legal articles comprised in the book lose their jurisdictional dimension and become some kind of instructions, where the element   of caution is prevailing. The relationship between Deuteronomy and teaching allows to distinguish and outline the elements of the process of teaching or widely understood process of education. The addressee is called by means of rhetoric to active and conscious participation in educational process. The method of education whose essence lies in repeating and reflecting upon the contents taught on various times of the day is supposed to help. Reminding of the events and their "realization", for example setting them in the cult, manifests the relationship between knowledge and practice as well as the expression of efficiency of knowledge itself. Passing the knowledge acquired to your sons also signifies the efficiency of knowledge and its connection with life. All of this takes place inside the religious and national community, as education through community, but also individual education. The uniqueness of this educational process is that the ultimate reference of all cautions and the ultimate "educator" is God Himself. And Deuteronomy itself incessantly interpreted, commented and "taken to hart, becomes the key means and didactic aid for educational process. At the same time, it is testimony to this process.